Effects of Exercise on Chemotherapy Completion and Hospitalization Rates: The OptiTrain Breast Cancer Trial. (7th August 2019) - Mijwel, Sara; Bolam, Kate A.; Gerrevall, Jacob; Foukakis, Theodoros; Wengström, Yvonne; Rundqvist, Helene
Abstract: Background: Exercise during chemotherapy is suggested to provide clinical benefits, including improved chemotherapy completion. Despite this, few randomized controlled exercise trials have reported on such clinical endpoints. From the OptiTrain trial we previously showed positive effects on physiological and health‐related outcomes after 16 weeks of supervised exercise in patients with breast cancer undergoing chemotherapy. Here, we examined the effects of exercise on rates of chemotherapy completion and hospitalization, as well as on blood cell concentrations during chemotherapy. Patients and Methods: Two hundred forty women scheduled for chemotherapy were randomized to 16 weeks of resistance and high‐intensity interval training (RT‐HIIT), moderate‐intensity aerobic and high‐intensity interval training (AT‐HIIT), or usual care (UC). Outcomes included chemotherapy completion, hospitalization, hemoglobin, lymphocyte, thrombocyte, and neutrophil concentrations during chemotherapy. Results: No significant between‐groups differences were found in the proportion of participants who required dose reductions (RT‐HIIT vs. UC: odds ratio [OR], 1.08; AT‐HIIT vs. UC: OR, 1.39), or average relative dose intensity of chemotherapy between groups (RT‐HIIT vs. UC: effect size [ES], 0.08; AT‐HIIT vs. UC: ES, −0.07). A significantly lower proportion of participants in the RT‐HIIT group (3%) were hospitalized during chemotherapy compared with UC (15%; OR, 0.20). A significantly lower incidence of thrombocytopenia was found for both RT‐HIIT (11%) and AT‐HIIT (10%) versus UC (30%; OR, 0.27; OR, 0.27). Conclusion: No beneficial effects of either RT‐HIIT or AT‐HIIT on chemotherapy completion rates were found. However, combined resistance training and high‐intensity interval training were effective to reduce hospitalization rates, and both exercise groups had a positive effect on thrombocytopenia. These are important findings with potential positive implications for the health of women with breast cancer and costs associated with treatment‐related complications. Abstract : The positive effect of supervised exercise in patients with breast cancer undergoing chemotherapy has previously been shown. This article focuses on the effects of exercise on chemotherapy completion and hospitalization rates, as well as blood cell concentrations during chemotherapy.